Seismic rehabilitation of reinforced concrete columns - Patrício Rocha (2006)
The main purpose of this paper is to present an experimental campaign of different strategies for the seismic retrofit of RC columns, comparing the obtained results with analytical methodologies, and evaluating benefits concerning their structural behaviour under the cyclic loading. The experimental campaign was conceived taking into account the typical constructions of the seventies, designed according to old codes without seismic considerations, and seeking the best structural retrofit technique to enable seismic behaviour improvement with acceptable financial resources. The setup of the RC columns experimental tests was specially designed to carry out biaxial bending with axial load, using two orthogonal and horizontal actuators and one vertical actuator (with a slide device to allow the top displacements of the column), though, at this stage, only uni-axial bending experimental results are available. The columns rehabilitation, improving the ductility or the strength characteristics, was obtained increasing the concrete ductility conditions, through efficient jacketing, or increasing the amount of longitudinal and transversal steel. The aim is, therefore, to contribute for developing and calibrating a procedure that enables the evaluation of the efficiency of the different retrofit solutions, their possibilities and fields of application. It was also an objective of this work to explore the possibility of use this retrofitting techniques on the improvement of buildings performance.